The Group-Theoretical Analysis of Nonlinear Optimal Control Problems with Hamiltonian Formalism - Özer, Teoman; Polat, Gülden Gün (Springer Science and Business Media LLC, 2019)
In this study, we pay attention to novel explicit closed-form solutions of optimal control problems in economic growth models described by Hamiltonian formalism by utilizing mathematical approaches...
Keywords: Maximum Principle; Dynamic Optimization; Theory of Lie Groups; Economic Growth Models; Nonlinear Optimal Control Problems; Hamiltonian Formalism; Pontryagin?s